Performance of a Machine Learning Algorithm on Lesions with a High Preoperative Suspicion of Invasive Melanoma - Filippos Giannopoulos; Martin Gillstedt; Sofia Lindskogen; John Paoli; Sam Polesie (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)